Optimization of Performance Parameters of an Off-Grid Wind Solar Hybrid Power System Using HOMER Pro for Enhanced Energy Reliability at Kashim Ibrahim University, Maiduguri - Hamidu, M. M.; Abdulrahman, H. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2026)
Kashim Ibrahim University, Maiduguri faces persistent energy shortages due to unreliable grid supply and reliance on diesel generators. Earlier proposals for stand alone solar PV systems overlooked wind resources and full techno-economic optimization, highlighting the need for a more resilient hybrid approach. This study aims to evaluate and optimize an off-grid wind–solar hybrid power system for reliable and sustainable electricity supply at Kashim Ibrahim University. The assessment was carried out using hourly electrical load data and validated site specific meteorological data, including solar irradiance, wind speed, and temperature, modeled and optimized in HOMER Pro software. The optimal configuration includes 9.25 MW PV, 678 kW wind, lead-acid storage, and a bidirectional converter, which could provide 100% renewable energy with negligible unmet load. With a levelized cost of energy (LCOE) of ₦85.18/kWh and a 3.9 year payback period, the system outperforms grid and diesel alternatives by producing 17.63 GWh yearly to satisfy the 3.21 GWh demand. Over a 25-year period, the system prevents more than 308,000 tonnes of CO₂ emissions and reduces air and noise pollution. Strong temperature resilience is confirmed by sensitivity analysis, where temperature variation between 25–35°C results in only a 3.5% reduction in energy production. The optimized wind–solar hybrid system offers a cost effective, reliable, and environmentally sustainable energy solution for institutional power supply in northeastern Nigeria. Phased implementation is recommended for Kashim Ibrahim University and other institutions facing persistent energy insecurity.